An evolutionary approach to the delimitation of labour market areas: an empirical application for Chile. Issue 4 (2nd October 2017) - Casado-Díaz, José Manuel; Martínez-Bernabéu, Lucas; Rowe, Francisco
ABSTRACT: An evolutionary approach to the delimitation of labour market areas: an empirical application for Chile. Spatial Economic Analysis . Labour market areas (LMAs) are argued to represent a more appropriate policy framework than administrative units for the analysis of spatial labour market activity. This article develops LMAs for Chile by applying an evolutionary computation approach. This innovative approach defines LMAs through an optimization process by maximization of internal cohesion, subject to restrictions of minimum levels of self-containment and population. To evaluate the appropriateness of the LMAs, comparative analyses are performed between alternative delimitations based on different parameter configurations of the proposed method versus administrative boundaries and the most widely used method for official LMA delimitation, the travel-to-work areas method.